Structural and dielectric properties of double perovskite lead free BiGdMnNiO6 electronic system. (2021) - Tripathy, A.; Das, S.N.; Bhuyan, S.; Choudhary, R.N.P.
Abstract: An effective as well as a simple method has been adopted to formulate a lead free BiGdMnNiO6 double perovskite electronic material. The synthesis has been carried out through the conventional high temperature ceramic processing route. The crystal structure realization has been confirmed with the help of powder X-ray diffraction method which shows that at room temperature the ceramic exhibits a monoclinic structure. To study the consequences of frequency and temperature on the conduction mechanism impedance spectroscopy methods have been used. The variations of tangent loss and dielectric at different frequencies have been carried out to study the capacitive behaviour of the ceramic material. The impedance analysis of the material signifies the existence of negative temperature coefficient. The important physiochemical properties associated with this compound may be very much essential in the development of next generation electronic devices.